Human platelet lysate-based nanocomposite bioink for bioprinting hierarchical fibrillar structures - Mendes, Bárbara B. (2020)
Three-dimensional (3D) bioprinting holds the promise to fabricate tissue and organ substitutes for regenerative medicine. However, the lack of bioactive inks to fabricate and support functional living constructs is one of the main limitations hindering the progress of this technology. In this study, a biofunctional human-based nanocomposite bioink (HUink) composed of platelet lysate hydrogels reinforced by cellulose nanocrystals is reported. When combined with suspended bioprinting technologies, HUink allows the biofabrication of 3D freeform constructs with high resolution and integrity, mimicking the hierarchical nano-to-macro fibrillary composition of native tissues. Remarkably, HUink supports bioprinting of stem cells with high viability immediately after extrusion and over long-term cell culture without the need for additional biochemical or animal-derived media supplementation. As opposed to typical polymer-based bioinks, the pool of growth factors, cytokines and adhesion proteins in HUink boosts cell spreading and proliferation, stimulating the fast production of cell-secreted extracellular matrix. This innovative bioprinting platform with unpaired biofunctionality allows the fabrication of complex freeform cell-laden constructs that can ultimately be applied in the development of xeno-free 3D tissue models for in vitro research or to develop tissue and organ surrogates for clinical applications.